Perbankan Syariah Dalam Perspektif Hukum Ekonomi Syariah - Tiurma P, Maria Eleos; B, Baidhowi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In this context, Shariah economic law has a crucial role for the running of Shariah banking. Sharia economic law itself is a collection of rules or norms derived from the Qur’an and Hadith, the purpose of which is to govern the reeconomic system of Muslims. The basic principles and especially in this law are the prohibition of usury / interest, interest / uncertainty and maysir / gambling, as well as encouraging mudharabah / sharing of profits. The research method adopted in compiling this article is literature study research method. Research is conducted by collecting, reviewing, and analyzing various written sources relevant to the researched topic. Shariah economic law is a collection of rules derived from the Qur'an, Hadith, and ijtihad of scholars, which regulates the Islamic economic system with key principles such as the prohibition of usury (interest), gharar (uncertainty), and maysir (gambling), as well as encouraging a system of sharing the results of al-Syrians in financial transactions. conventional banking by emphasizing the values of fairness and partnership in transactions.